Fulminant group A streptococcal necrotizing fasciitis presenting as severe calf pain after pharyngitis in an adolescent: a case report - Lisa Roncoroni; Jan Kühle; Lampros Kousoulas; Katharina Müller-Peltzer; Dawid L. Staudacher (Frontiers in Medicine, 2026)
Background Invasive Group A Streptococcus (GAS) infection can rapidly progress to life-threatening conditions, including necrotizing fasciitis (NF) and streptococcal toxic shock syndrome (STSS). While typically associated with cutaneous breaches or underlying comorbidities, hematogenous seeding following primary pharyngeal infection is a rare but documented phenomenon. Early diagnosis is often complicated by subtle skin changes and the rarity of the disease. Case A previously healthy 17-year-old female presented with acute pain of the right calf accompanied by severe tachycardia and rapidly progressive hypotension. Notably, she had experienced acute pharyngitis symptoms approximately two days prior to the onset of her soft tissue pain. Physical examination revealed no typical cutaneous hallmarks of necrotizing fasciitis, such as severe erythema, skin discoloration or crepitus. Complicating the diagnosis, radiological imaging strongly suggested acute cholecystitis as an alternative potential source of her systemic sepsis. Due to the absence of conventional typical signs and the presence of a confounding abdominal focus, establishing a diagnosis of NF proved to be an exceptional clinical challenge; the correct diagnosis was ultimately made possible only thanks to a rapid, multidisciplinary discussion involving emergency medicine, radiology and surgical teams. Emergency surgical exploration of the right lower extremity confirmed widespread necrosis of the superficial fascia and subcutaneous tissue. Cultures from both the deep fascial tissue and blood grew monomicrobial Streptococcus pyogenes . The absence of any local skin trauma supported a diagnosis of hematogenous seeding from the recent pharyngeal infection. The patient was aggressively managed in the intensive care unit with multiple rounds of emergency surgical debridement, targeted intravenous antibiotic therapy (high-dose penicillin and clindamycin), vasoactive support, and adjuvant intravenous immunoglobulin (IVIG) therapy. Following a prolonged hospital course, the patient stabilized, recovered completely, and was successfully discharged. Conclusion Severe pain disproportionate to skin findings after a recent streptococcal infection should prompt consideration of necrotizing fasciitis, even in otherwise healthy adolescents. Early surgical exploration and source control remain central to management, while adjunctive IVIG may be considered in selected patients with suspected streptococcal toxic shock syndrome.